2015
DOI: 10.1007/s00345-015-1613-5
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife stereotactic radiotherapy for isolated recurrence in the prostatic bed

Abstract: Our experience shows that SBRT with CyberKnife for isolated nodal relapse is a safe and well-tolerated treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 26 publications
3
57
1
Order By: Relevance
“…Jereczek‐Fossa et al in 2012 published a retrospective analysis of 34 patients treated with SSRT (30 Gy in five fractions), including 19 cases of re‐irradiation for local recurrence, and reported a 30‐month PFS rate of 42.6%. Another monocentric case series was published by the University of Florence in 2016, reporting data on 16 patients treated with SSRT and showing a significant biochemical response in all but one patient . However, these series included patients undergoing re‐irradiation and patients with regional and/or nodal metastases, and a direct comparison with present analysis is difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Jereczek‐Fossa et al in 2012 published a retrospective analysis of 34 patients treated with SSRT (30 Gy in five fractions), including 19 cases of re‐irradiation for local recurrence, and reported a 30‐month PFS rate of 42.6%. Another monocentric case series was published by the University of Florence in 2016, reporting data on 16 patients treated with SSRT and showing a significant biochemical response in all but one patient . However, these series included patients undergoing re‐irradiation and patients with regional and/or nodal metastases, and a direct comparison with present analysis is difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Our excellent rates of GU and GI side effects confirm the good profile of toxicity reported also by other investigators in smaller series. 17,18,20,21,23,25 For example, Leroy et al 20 in a series of 23 patients treated with SBRT (36 Gy in 6 fractions) did not observe Grade 4 or 5 toxicity. Importantly, in our series no patient experienced urinary incontinence, a typical complication of other salvage local therapies.…”
Section: Discussionmentioning
confidence: 98%
“…The efficacy of salvage reirradiation for locally recurrent PCa has been evaluated by several investigations. [14][15][16][17][18][19][22][23][24][25][26][28][29][30][31][32][33][34] The first report on re-EBRT by Vavassori et al 15 including six cases treated by CyberKnife, showed the feasibility of reirradiation with an acceptable rate of acute and early chronic toxicity (median follow-up was 11.3 months). These preliminary findings were then confirmed by the successive series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous studies on reirradiation for various tumors sites, experience in retreatment of prostate cancer is very limited and includes mainly brachytherapy series [1]. Since the review by Alongi et al in 2013 [1], a couple of new series have been published and show that both technology and radiobiology play a role [2,3]. Using advanced imaging (recurrence identified by magnetic resonance, staging based on [ 18 F]-fluorocholine positron emission tomography), highly selective radiotherapy modalities (stereotactic body radiotherapy and image-guided intensity-modulated radiotherapy), and extreme hypofractionation (doses > 6 Gy/fraction), Janoray et al showed that reirradiation is safe and may offer a medium-term cure in a good proportion of patients.…”
Section: Expert's Summarymentioning
confidence: 99%